2012
DOI: 10.1007/s00259-011-2049-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative volumetric analysis of gliomas with sequential MRI and 11C-methionine PET assessment: patterns of integration in therapy planning

Abstract: The metabolically active tumour volume observed in (11)C-methionine PET differs from the volume of MRI by showing areas of infiltrative tumour and distinguishing from non-tumour lesions. Differences in (11)C-methionine PET/MRI integration patterns can be assigned to tumour grades according to the WHO classification. This finding may improve tumour delineation and therapy planning for gliomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 33 publications
(77 reference statements)
1
39
1
3
Order By: Relevance
“…In vivo, the level of proliferation, as assessed by Ki67 staining, was associated with histologic characteristics in a rat glioblastoma model (23). In human patients, histologic profiles of suspected glioblastomas were in accordance with 11 C-methionine uptake levels (25), and 11 C-methionine uptake was strongly correlated with proliferation (26). In our study, increased staining was observed in tumor foci on the histologic sections of femurs labeled with Ki67.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, the level of proliferation, as assessed by Ki67 staining, was associated with histologic characteristics in a rat glioblastoma model (23). In human patients, histologic profiles of suspected glioblastomas were in accordance with 11 C-methionine uptake levels (25), and 11 C-methionine uptake was strongly correlated with proliferation (26). In our study, increased staining was observed in tumor foci on the histologic sections of femurs labeled with Ki67.…”
Section: Discussionmentioning
confidence: 99%
“…[37,38] Unfortunately, the short 20-minute half-life of the 11 C isotope precludes its use at centers that lack access to an onsite cyclotron. In contrast O-(2-18 F-fluoroethyl)-L-tyrosine ( 18 F-FET), another amino acid tracer, has a much longer half-life of 109 minutes allowing for more widespread use.…”
Section: Diffusion-weighted Imaging (Dwi)mentioning
confidence: 99%
“…Because contrast enhancement only depicts tumor areas with a disrupted blood-brain barrier, it might not show invasive areas at the border zone of lesions. 1 The only tool other than iMRI established in clinical routine that shows residual tumor in situ is 5-ALAbased fluorescence. Preliminary data comparing 5-ALA fluorescence with preoperative MRI suggest a higher sensitivity for tumor tissue detection.…”
Section: The Gold Standard To Assess Eor In Hggs and Mets Is Postopermentioning
confidence: 99%